Targeting S100A1 in heart failure - Ritterhoff, Julia; Most, Patrick (Gene therapy, 2012)
Heart failure (HF) is the common endpoint of many cardiovascular diseases with a 1-year survival rate of about 50% in advanced stages. Despite increasing survival rates in the past years, current standard therapeutic strategies are far away from being optimal. For this reason, the concept of cardiac gene therapy for the treatment of HF holds great potential to improve disease progression, as it specifically targets key pathologies of diseased cardiomyocytes (CM). The small calcium (Ca2+)-binding protein S100A1 presents a promising target for cardiac gene therapy, as it has been identified as a central regulator of cardiac performance and the Ca2+-driven network within CM. S100A1 was shown to regulate sarcoplasmic reticulum, sarcomere and mitochondrial function by modulating target protein activity. Furthermore, deranged S100A1 expression has been linked to HF in human ischemic and dilated cardiomyopathies as well as in various HF animal models. Proof-of-concept studies in small and large animal models as wells as in human failing CM could demonstrate feasibility and efficacy of S100A1 genetically targeted therapy. This review summarizes the developmental steps of S100A1 gene therapy for the implementation into first human clinical trials.